The efficacies and biomarker investigations of antiangiogenic agents and PD-1 inhibitors for metastatic soft tissue sarcoma: A multicenter retrospective study - Liu, Zhiyong; Wang, Xin; Wang, Jiaqiang; Zhang, Peng; Li, Chao; Wang, Bangmin; Gao, Songtao; Liu, Oufei; Yao, Weitao (Frontiers in Oncology, 2023)
Objective To investigate the efficacy and safety of antiangiogenesis-immunotherapy in patients with advanced STS in China, and to explore the potential factors of prognosis. Patients and Methods This retrospective study was conducted at three hospitals in China, and the patients with metastatic STS who were ineligible for or declined anthracycline-based chemotherapy received antiangiogenic agents (anlotinib or apatinib) plus programmed death-1 (PD‐1) inhibitors (camrelizumab or sintilimab) between June 2019 and May 2022. The primary endpoint was progression-free survival rate at 6 months (6-month PFSR), and the secondary endpoints were objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), and overall survival (OS) and toxicity. Biomarkers that might affect the prognosis were explored. Results Thirty-nine patients were included: five patients with alveolar soft tissue sarcoma (ASPS) and 34 with non-ASPS. With a median follow-up of 18.2 months, the 6-month PFSR was 51.3%, with the ORR of 20.5% and DCR of 76.9%. The median PFS and OS were 7.0 months and 17.2 months. The 6-month PFSR for patients with ASPS and non-ASPS was 80.0% and 47.1%, respectively. The most common adverse events were hypothyroidism (56.4%), followed by fatigue (46.2%), and hypertriglyceridemia (43.6%). No treatment-related deaths were observed. Patients with low baseline NLR (NLR < 4) had better 6-month PFSR than those with high NLR (NLR ≥ 4) (82.4% vs. 31.6%). Conclusion Antiangiogenic agents plus PD-1 inhibitors showed acceptable toxicity and promising efficacy in patients with advanced STS, especially patients with ASPS, and a low NLR might serve as a reliable biomarker for 6-month PFSR, PFS, and OS. It provides a reference for randomized controlled trials.